KOMPONEN HAYATI YANG SERING DIJUMPAI DI PEKARANGAN KASUS TELUKNAGA, CITEUREUP DAN PACET - D.S. SASTRAPRADJA; M. IMELDA; S. ADISOEMARTO (Research Center for Biology-Indonesian Institute of Sciences, 1985)
D.S. SASTRAPRADJA, M. IMELDA & S. ADISOEMARTO.1985. Biological components frequently encountered in the kitchen gardens : thein Teluk Naga, Citeureup and Pacet.Berita Biologi 3 (2) : 25 - 36. Based on the grouping into ornamental plants, fruit trees, vegetables, medicinal plants, industrial plants and tu'oer crops, the vegetation of kitchen gardens showed uniform peicentage in the three study localities.The highest was occupied by ornamental plants, followed by lruit trees and vegetables, then industrial and medicinal plants, while the least was tuber crops.However, the three localities showed variations in frequency classes of each plant group, whilst in total, these frequency classes were uniform. Animal comiponents in the kitchen gardens were represented by variaous numbers of species in the three localities.In any case, chickens were the dominant group of animals, These birds were raised traditionally in most cases.Of the decomposing insects, each of the three localities showed their specificities. The coastal area was dominated by underground beetles, the interior low land by termites and the higher altitude by dung beetles. Different compositions were showed also by the insect pest groups.